Effect of group music therapy on state-anxiety and well-being levels of oncology patients undergoing chemotherapy: a multi-center randomized clinical trial - Ettenberger, Mark; Reyes-Aragón, Laura; Díaz, Ana María; Suárez, Raúl; Amarillo, Moshé; Naranjo, Mariana; Colmenares-Mejía, Claudia C. (Frontiers in Psychiatry, 2025)
BackgroundCancer patients undergoing chemotherapy may experience several mental health challenges, including increased levels of anxiety and affected well-being. Music therapy and other music-based interventions have previously been applied to improve patient mental health during chemotherapy, but multi-site RCTs that report live group music therapy interventions are scarce.MethodsThis is a multi-site randomized clinical trial (RCT) with two arms: a single live group music therapy session + standard care and standard care alone. Primary outcome measure was the State-Trait Anxiety Inventory (STAI), and secondary outcome measures were the Well-being Numerical Rating Scales (WB-NRSs). Between-group differences in STAI and WB-NRSs scores were analyzed using the Wilcoxon rank-sum test. Intra-individual pre-post changes were assessed with the Wilcoxon signed-rank test. This study follows the CONSORT guidelines for reporting RCTs.ResultsA total of 110 patients were included in this study. Results showed a statistically significant reduction of state anxiety from pre- to post-intervention for the music therapy group (p<0.001), but not for the control group. Between-group analysis showed significantly lower post-intervention STAI scores in the music therapy group as compared to the control group (p<0.001). With respect to well-being, only the music therapy group had statistically significant increases in all dimensions of well-being within-group from pre-to post timepoints, and between-group analysis showed statistically significant post-intervention differences in psychological (p = 0.005) and general well-being (p = 0.030) favoring the music therapy group. Effects of hospital sites on the outcomes were not significant.DiscussionThe results suggest that group music therapy during chemotherapy is a safe and effective strategy to improve mental health and well-being in cancer patients. To our knowledge, this is the first multicenter RCT on group music therapy during chemotherapy in Colombia. Future studies should aim at integrating caregivers of chemotherapy patients and seek expansion to an international multi-site RCT.